Some problems of polymer flow in injection mould - Sikora, R.; Bociąga, E. (Polimery, 2022)
The descriptions of liquid polymer flow in the injection mold channels, presented in the literature data, have been discussed. The flow is unstable and non-isothermal. Most often the symmetrical model is used to describe it although this model is true only at determined stable conditions. When thermal or kinetic conditions at both sides of the channel vary (e.g. because of the differences of temperature or surface roughness) thermokinetic flow asymmetry occurs. This asymmetry may be also caused by the change of flow direction in the channels e.g. in the area where the sprue joins the runner or in the cavities with inserts, bosses and ribs. In multicavity molds the polymer stream can change the direction even several times that lead to non-uniform filling of cavities. As well the weld lines areas are areas of polymer flow disturbances. Asymmetrical and non-uniform flow affects the injection molding efficiency evaluated on the basis of determinations of functional properties and surfaces qualities of molded parts